RPV Long Terra Operation: Open Issues - Ballesteros, A.; Altstadt, E. (Проблемы прочности, 2013)
This paper presents and describes key open issues which are being debated nowadays by experts in the field, and for which clarification is essential for a safe operation of the nuclear power plants during life extension. Notably: late blooming effects in low Cu steels; effects of Cu, Ni, Mn, and P on the irradiated microstructure and on hardening and embrittlement; use of material test reactor data for assessment in power reactors (including flux and spectrum effects); Master Curve versus Unified Curve and fracture toughness behavior of highly irradiated material; embrittlement in RPV zones out of the traditional beltline (“the expanding beltline”); embrittlement trend curves at high neutron fluence, where data are scarce; re-embrittlement after annealing. Описаны актуальные проблемы обеспечения безопасной работы АЭС при продлении сроков
эксплуатации, которые широко обсуждаются экспертами данной отрасли. К ним, в частности, относятся: эффекты запаздывания в сталях с низким содержанием меди влияние Cu,
Ni, Mn и P на микроструктуру, упрочнение и охрупчивание облученных сталей применимость
результатов испытаний, полученных в исследовательском атомном реакторе, к промышленным реакторам, включая эффекты флакса и спектра сопоставление Мaster-кривой с
унифицированной кривой, а также особенности разрушения высокооблученных материалов;
охрупчивание материалов в зонах корпусов реакторов вне традиционных участков; построение трендовых кривых охрупчивания для высокого флюенса нейтронов при малом объеме
данных; повторное охрупчивание после отжига. Описано актуальні проблеми забезпечення безпечної роботи АЕС при продовженні термінів експлуатації, які широко обговорюються експертами даної
галузі. До них, зокрема відносяться: ефекти запізнювання в сталях із низьким
вмістом міді; вплив Cu, Ni, Mn і P на мікроструктуру, зміцнення і окрихчування опромінених сталей; використання результатів випробувань, отриманих
у дослідном атомному реакторі, до промислових реакторів, включаючи ефекти флакса і спектра; зіставлення Мaster-кривої з уніфікованою кривою, а
також особливості руйнування високоопромінених матеріалів; окрихчування
матеріалів у зонах корпусів реакторів поза традиційними участками побудова трендових кривих окрихчування для високого флюенса нейтронів за
малого об’єму даних; повторне окрихчування після відпалу.